RESPONSE OF PANT PRABHAT GUAVA TREES TO FOLIAR SPRAYS OF ZINC, BORON, CALCIUM AND POTASSIUM AT DIFFERENT PLANT GROWTH STAGES - JITENDRA KUMAR,; RAJESH KUMAR,; RATNA RAI,; D. S. MISHRA, (The Bioscan, 2015)
The experiment comprised foliar sprays of boron, zinc, calcium and potassium at two stages, viz., at fruit set or two weeks after fruit set on guava plant. The foliar fertilization showed an increasing trend towards plant height (12.17% with 0.03% Zn two weeks after fruit set), fruit weight (150g with 0.03% B two weeks after fruit set), volume (147.67 with 0.03% B two weeks after fruit set) and yield (52.50 kg/tree with 0.01% Zn two weeks after fruit set). Similarly, pulp : seed ratio (94.88 with 0.5% K two weeks after fruit set), TSS (11.500Brix with 0.5% K on fruit set) and total sugars (7.36% with 0.5% K two weeks after fruit set) also increased by foliar fertilization while it showed a trend towards decresing per cent fruit drop (5.90% with 0.03% Zn two weeks after fruit set) and acidity content (0.26% with 0.5% K two weeks after fruit set). The seed hardness (11.48 kg with 0.01% B on fruit set) showed non uniform pattern. The stage of growth also affected the growth, yield and quality of guava fruits. Results indicated that foliar fertilization when done two weeks after fruit set influenced plant growth and fruit quality.